Isothermal Aging Effect on Sn-58Bi Solder Interconnect Mechanical Shear Stability - Waduge, Gihan Dodanduwa; Baty, Greg; Lee, Young-woo; Lee, Tae-Kyu (Journal of electronic materials, 2022)
Use of low melting temperature solder (LTS) materials in interconnect devices is a recent application as they lower the challenges of high reflow peak temperature-induced package warpage during assembly. A good candidate to overcome this challenge is a eutectic Sn-Bi system solder, with a melting temperature of 138°C and a reflow peak assembly temperature of around 185°C. However, Bi causes joint hardening and is prone to brittle fractures under mechanical bend and shock. Therefore, it is critical to understand mechanical properties of Sn-58Bi solder joints under conditions of end-use condition and applications. In this study, a series of isothermally aged 300- μ m-diameter solder balls attached to a NiAu pad surface finish, are subject to single-ball shear tests after up to 500 h aging at room temperature, 100°C and −25°C. Single-ball shear tests were performed using a multi-bond tester with 10- μ m shear height and two shear speed condition, 10 μ m/s and 100 μ m/s. The maximum shear load and the distance to the peak shear load were measured to observe the deformation behavior change. Comparative testing was also conducted for Sn-1.0Ag-0.5Cu (wt.%) aged samples for comparison. A decrease in maximum shear strength and loss of ductility with 100°C isothermal aging, opposite to an increase in ductility with room temperature isothermal aging were observed. Isothermally aged Sn-58Bi samples reveal further loss of ductility compared to SAC105 which show increase in ductility. This phenomenon is due to the increased Bi solubility into Sn at a higher temperature range. The deformation behavior for both Sn-58Bi and SAC105 were observed and discussed on partially sheared solder joints using EBSD analysis.